Visualisasi Data Kependudukan Menggunakan Power Business Intelligence (Studi Kasus Kelurahan Sukamiskin Kecamatan Arcamanik Kota Bandung) - Sri Bekti Handayani Ningsih; Iyat Ratna Komala; Leni Nurhayati; Maya Suhayati (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Sukamiskin Village is one of the villages in the Arcamanik sub-district of Bandung City. Population data is very useful as a basis for policy making to improve the economy, determine security facilities, improve infrastructure, and so on. One of the community institutions that have the task of collecting population data is the Rukun Tetangga (RT) management. The application of the Power Business Intelligence (Power BI) application in analyzing population data in Sukamiskin Village by taking sample data in Sukamiskin village RT.01 RW.06. The population data analyzed includes information such as population size, age distribution, education level, gender, marital status and employment status. This study aims to provide a clear picture or visualization of population data in Sukamiskin village RT.01 RW.06 using the Microsoft Power BI application with the stages of collecting data, entering data, modeling data, and visualizing data. The results of this research are in the form of a dashboard/summary report and detailed report on the population data of the Sukamiskin village RT.01 RW.06. The results of the analysis show that Power BI is able to present data comprehensively and assist in strategic decision making at the village level. The implementation of Power BI is expected to increase the benefits of population data and accelerate the process of